Dualism of Remarkable Magnesium Ion Conduction with Low Activation Energy over a Wide Temperature Range versus Limited Stability of the Hybrid Composite Electrolyte Mg-MOF-74/MgX2/Propylene Carbonate - Maile, Ruben; Wei, Zhixuan; Achazi, Andreas Johannes; Wang, Kangli; Henkel, Pascal; Mollenhauer, Doreen; Janek, Jürgen; Müller-Buschbaum, Klaus; Justus Liebig University Giessen (My University, 2024)
A metal–organic framework (MOF) quasi-solid-state Mg2+-ion conductor is prepared with a conductivity of 0.6 × 10−4 S cm−1 already at room temperature. Mg-MOF-74 acts as host for MgX2 (X = Cl−, Br−, BF4−) dissolved in propylene carbonate, leading to dry free-flowing powders with liquid electrolyte exhibiting low activation energy of 0.2 eV with Arrhenius-type behavior (233–333 K). Different halides and pseudohalides reveal an influence of the anions on ionic conductivity, activation energy, and chemical stability. High transference numbers 0.45–0.80 for Mg2+ ions are recorded, being among the highest reported with small and low-cost halides. Against magnesium, an insulating solid electrolyte interface layer forms that prevents a steady-state and full-MOF decomposition, as shown by powder X-ray diffraction, FTIR, and Raman spectroscopy. Comparison with pure propylene carbonate shows that the electrolyte is enhanced by MOF addition. Computational studies using density functional theory (DFT) calculations of complexes in solution indicate correlations between the activation energy for Mg2+ migration through the MOF and the Gibbs energy needed to form charged Mg compounds in solution. Furthermore, DFT calculations of complexes within the MOF pore reveal variations in binding energy and charge transfer correlating with experimental transference numbers. Altogether, the high potential of MOFs for quasi-solid-state electrolytes with multivalent cations stability issues are illuminated.
Keywords: ddc:540